PENGEMBANGAN MEDIA PEMBELAJARAN ISPRING SUITE MATERI RUKHSAH UNTUK MENINGKATKAN HASIL BELAJAR PAI SISWA - Hadi, Fida Rahmantika; Ardianzah, Ferri; Chaterina, Desida Bella (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Innovation in the field of education and learning increasingly involves the use of electronic technology, both in the form of media and methods. To make learning more engaging and improve students’ learning outcomes, it is necessary to develop innovative learning media, specifically the development of Islamic Education (PAI) learning media using iSpring Suite. This study aims to examine the development process, feasibility, and effectiveness of using iSpring Suite-based learning media on the topic of rukhsah in improving students’ PAI learning outcomes. This research employed a Research and Development (R&D) design using the Borg and Gall development model. The sample consisted of 26 students from class VII A. Data collection techniques included questionnaires, tests, and interviews, while data analysis was conducted using descriptive analysis and t-test analysis to determine differences in learning outcomes before and after the implementation of iSpring Suite-based PAI learning media on the topic of rukhsah. The results of the development process showed that the validation scores were 92.5% from media experts, 95% from material experts, and 90% from learning experts, all of which fall into the “very feasible” category. Student responses yielded a score of 82%, indicating a “very good” category. The normality test indicated that the data were not normally distributed; therefore, non-parametric statistical analysis using the Wilcoxon test was applied. The Wilcoxon test results showed a significance value of <0.05, indicating that the hypothesis was accepted and that the iSpring Suite-based learning media on rukhsah is effective in improving students’ learning outcomes. Keywords: Learning Media Development, iSpring Suite, Rukhsah, Learning Outcomes